Antigen-specific downregulation of miR-150 in CD4 T cells promotes cell survival - Ménoret, Antoine; Agliano, Federica; Karginov, Timofey A.; Karlinsey, Keaton S.; Zhou, Beiyan; Vella, Anthony T. (Frontiers in Immunology, 2023)
MicroRNA-150 (miR-150) has been shown to play a general role in the immune system, but very little is known about its role on CD4+ T cell responses. During T cell responses against superantigen Staphylococcal Enterotoxin A, miR-150 expression was down-regulated in antigen-specific CD4+ T cells but up-regulated in CD8+ T cells. CD4+ and CD8+ T cell clonal expansion was greater in miR-150-KO mice than in WT mice, but miR-150 selectively repressed IL-2 production in CD4+ T cells. Transcriptome analysis of CD4+ T cells demonstrated that apoptosis and mTOR pathways were highly enriched in the absence of miR-150. Mechanistic studies confirmed that miR-150 promoted apoptosis specifically in antigen-specific CD4+ T cells, but not in bystander CD4+ nor in CD8+ T cells. Furthermore, inhibition of mTOR-linked mitochondrial superoxidedismutase-2 increased apoptosis in miR-150-/- antigen-specific CD4+ T. Thus, miR-150 impacts CD4+ T cell helper activity by attenuating IL-2 production along with clonal expansion, and suppresses superoxidedismutase to promote apoptosis.